Laparoscopic-Assisted Removal of Bleeding Mesenteric Meckel’s Diverticulum in Children: Case Series and Systematic Review - Veronica Vitali; Giulia Fusi; Alessandro Raffaele; Maria Ruffoli; Simonetta Mencherini; Carmine Noviello; Gian Battista Parigi; Mirko Bertozzi (Gastrointestinal Disorders)
Background: Meckel’s diverticulum on the mesenteric side has been reported only as case reports in the literature and presents a diagnostic challenge, with ultimate recognition often taking place intraoperatively. We describe a case series of children with mesenteric Meckel’s diverticulum (MMD) treated at our institution, along with the results of a systematic review of the literature. Methods: Our experience on MMD was analyzed along with a systematic literature review performed according to PRISMA criteria. We identified studies published from 1941 to 2023 from PubMed, EMBASE, SCOPUS, and WOS. Search terms were variations of “Meckel”, “diverticulum”, and “mesenteric”. Inclusion criteria were patients < 18 years of age and articles written in English. Results: A total of three cases of MMD were observed and treated in our hospital. The mean age was 7.6 years. The most common symptoms were rectal bleeding and abdominal pain. Diagnostic workup included ultrasound and both upper and lower endoscopy. Surgery was performed by the laparoscopy-assisted technique. One case had to be reoperated due to postoperative intestinal occlusion. The mean length of hospital stay was 9.3 days. The literature search yielded 795 citations; out of the 590 papers remaining after the exclusion of 205 duplications, only 15 papers matched the inclusion criteria and were included and analyzed. Conclusions: MMD remains a rare and elusive pathology, sharing with its normal counterpart symptoms and signs. In our experience, and in the more recent literature, laparoscopy-assisted surgery appears safe and effective both for final diagnosis and definitive treatment.